2018
DOI: 10.1186/s40163-018-0081-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding site selection of illegal border crossings into a fenced protected area: a rational choice approach

Abstract: This study investigates illegal border crossings by rhino poachers into a fenced reserve in South Africa, comparing journeys to and after crime using a rational choice approach. Using various regression models, our analysis indicates poachers prefer to enter and exit the reserve near high rhino densities, while high road densities outside the reserve increase the odds of an illegal entry. The results also show that half of the incursions occurred at a single location, leading us to describe the special circums… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Quantitative methods remain an important tool in wildlife crime studies. Customs seizure trends (Petrossian et al, 2016;Van Uhm, 2016), the effect international wildlife commodity bans have on poaching (Lemieux and Clarke, 2009), poacher preferences for illegal border crossings into protected areas (Van Doormaal et al, 2018), modeling the most efficient wildlife patrol regimes in protected areas (Fang et al, 2017), and modeling enforcement and compliance in conservation (Keane et al, 2008) have all been studied quantitatively. However, qualitative methods provide a means to both complement and increase the robustness of existing natural science knowledge (Drury et al, 2011;Moreto, 2016) and to concentrate emphasis on the contextual factors and details of crime commission.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative methods remain an important tool in wildlife crime studies. Customs seizure trends (Petrossian et al, 2016;Van Uhm, 2016), the effect international wildlife commodity bans have on poaching (Lemieux and Clarke, 2009), poacher preferences for illegal border crossings into protected areas (Van Doormaal et al, 2018), modeling the most efficient wildlife patrol regimes in protected areas (Fang et al, 2017), and modeling enforcement and compliance in conservation (Keane et al, 2008) have all been studied quantitatively. However, qualitative methods provide a means to both complement and increase the robustness of existing natural science knowledge (Drury et al, 2011;Moreto, 2016) and to concentrate emphasis on the contextual factors and details of crime commission.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also shown that poachers typically offend near edges like park boundaries (Watson et al, 2013), thus the boundaries for this study were operationalized as proximity. Because known or high target densities, for both flora (Young et al, 2011) and fauna (Critchlow et al, 2015; Rashidi et al, 2016; van Doormaal et al, 2018), have been shown to correlate with future illegal activity, animal sightings, previous flora incidents, and previous fauna incidents were all operationalized as density. Finally, conservation posts were operationalized as proximity because previous empirical research has shown that illegal activity often occurs in close distance to these locations (Jenks et al, 2012; Maingi et al, 2012; Rashidi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…An investigation of elephant poaching in Kenya found that elephant population density was a significant predictor in poaching behaviors, which could be due to having a greater “harvest” relative to the effort involved (Rashidi et al, 2016). In a study by van Doormaal and colleagues (2018), rhinoceros poaching in the northeastern part of South Africa was more likely to occur in areas of higher rhinoceros’ density. However, high-density targets may only increase the likelihood of certain poaching activities over others.…”
Section: Environmental Crime In Protected Areas: Situational Risk Facmentioning
confidence: 93%
See 2 more Smart Citations